Effectiveness and Safety Profile of Cisplatin Versus Nab-Paclitaxel Concomitant Chemoradiotherapy in Postoperative Early-Stage Cancer of Cervix - Bashir, Aalia; Hassan, Muhammad Junaid; Siddque, Anam (Biological and Clinical Sciences Research Journal, 2025)
Cervical cancer is a prevalent gynecologic malignancy with significant morbidity and mortality. Concomitant chemoradiotherapy remains the cornerstone of treatment for locally advanced stages. Cisplatin is the standard radiosensitizer, but alternative agents such as nab-paclitaxel may offer comparable efficacy with fewer side effects. Objective: To compare the effectiveness and safety profile of concomitant cisplatin versus nab-paclitaxel chemotherapy in patients with locally advanced cervical cancer. Methods: A retrospective study was conducted at the Oncology Department, Nishtar Hospital, Multan, from March 2023 to March 2025. A total of 100 women with stage I or II cervical cancer who had undergone radical pelvic surgery were included. All patients received adjuvant chemoradiotherapy 4–6 weeks postoperatively. External beam radiotherapy was administered at doses of 45–58.8 Gy over 5–5.6 weeks (1.8–2.1 Gy per fraction, five days per week). Patients were divided into two groups: Group A (n=50): Received cisplatin (40 mg/m² IV weekly). Group B (n=50): Received nab-paclitaxel (100 mg IV weekly). Overall survival (OS), progression-free survival (PFS), and treatment-related adverse effects were assessed. Statistical analysis was performed using hazard ratios (HR) with 95% confidence intervals (CI) and p-values, with significance set at <0.05. Results: Both treatment groups demonstrated comparable outcomes in terms of OS (HR: 0.89; 95% CI: 0.061–14.10; p=0.85) and PFS (HR: 0.98; 95% CI: 0.11–15.53; p=1.0). The 2-year OS was 98% in the cisplatin group and 97% in the nab-paclitaxel group. PFS at 2 years was 98% for both groups. Hematological toxicity and gastrointestinal side effects were significantly higher in the cisplatin group (p<0.05), whereas alopecia was more prevalent in the nab-paclitaxel group. No treatment-related mortality was observed. Conclusion: Nab-paclitaxel combined with radiotherapy is a viable and effective alternative to cisplatin in the management of early-stage cervical cancer. It offers comparable survival outcomes with a more favorable safety profile, particularly concerning hematologic and gastrointestinal toxicity.